2019
DOI: 10.1016/j.nicl.2019.101689
|View full text |Cite
|
Sign up to set email alerts
|

Anodal tDCS modulates cortical activity and synchronization in Parkinson's disease depending on motor processing

Abstract: BackgroundTranscranial direct current stimulation (tDCS) may alleviate motor symptoms in Parkinson's disease (PD). However, the neurophysiological effects of tDCS on cortical activation, synchronization, and the relation to clinical motor symptoms and motor integration need characterization.ObjectiveWe aimed to explore the effect of tDCS over the left sensorimotor area on clinical motor outcome, right hand fine motor performance as well as cortical activity and synchronization in the high beta range.MethodsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 82 publications
0
26
0
Order By: Relevance
“…At the whole-brain level, Wu et al 63 identified an increase in EEG coherence after applying stimulation over the left dorsolateral prefrontal cortex among 5 patients with disorders of consciousness. In contrast, another study of a larger sample size conducted by Schoellmann et al 55 found no significant differences between active and sham tDCS groups in rsFC, as indicated by imaginary corticocortical coherence across beta frequency bands among patients with Parkinson’s disease.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…At the whole-brain level, Wu et al 63 identified an increase in EEG coherence after applying stimulation over the left dorsolateral prefrontal cortex among 5 patients with disorders of consciousness. In contrast, another study of a larger sample size conducted by Schoellmann et al 55 found no significant differences between active and sham tDCS groups in rsFC, as indicated by imaginary corticocortical coherence across beta frequency bands among patients with Parkinson’s disease.…”
Section: Resultsmentioning
confidence: 83%
“…The included RCTs involved 348 patients in total from different age groups who suffered from a broad range of neurological disorders, including fibromyalgia, 49 inflammatory bowel disorder 50 and neuropsychiatric disorders (ie, schizophrenia, 51 , 52 substance abuse 53 ), neurodegenerative disorders (ie, multiple sclerosis, 54 Parkinson’s disease, 55 primary progressive aphasia 56 ), neurodevelopmental disorders (ie, attention-deficit/hyperactivity disorder 57 , 58 ), stroke, 59 , 60 and disorders of consciousness. 61 These studies adopted a great variety of tDCS protocols and adopted a variety of rsFC analytic methods.…”
Section: Resultsmentioning
confidence: 99%
“…), Parkinson's disease (Schoellmann et al . ), depression (Brunoni et al . ) and schizophrenia (Andrade, ).…”
Section: Introductionmentioning
confidence: 99%
“…For stroke patients, tDCS increased their hand–eye coordination ( Lefebvre et al, 2015 , 2017 ) and dexterity ( Lindenberg et al, 2010 , 2012 ; Nair et al, 2011 ; Khan et al, 2015 ; Zheng and Schlaug, 2015 ; Allman et al, 2016 ; Lee et al, 2018 , 2019 ), which could last for 1 week to 2 months. Two studies ( Del Felice et al, 2019 ; Schoellmann et al, 2019 ) have investigated tES on PD patients and have demonstrated it could improve the motor symptoms and modulate the brain oscillatory activity. These findings indicate the potential facilitation effects of tES on stroke recovery and PD symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…It revealed that tDCS increased functional connectivity within the premotor, motor, and sensorimotor areas during voluntary hand movements in the high-gamma band (60–90 Hz). Schoellmann et al (2019) discovered a reduction of beta rhythm coherence in PD patients after tDCS. Because excessive beta synchronization in the beta range is a marker in PD patients, these findings could indicate the potential application of tDCS in alleviating PD symptoms.…”
Section: Eegmentioning
confidence: 98%